2021
DOI: 10.1155/2021/2756666
|View full text |Cite
|
Sign up to set email alerts
|

Pushed SOLID: Deploying SOLID in Smartphones

Abstract: Personal information has become one of the most valuable coins on the Internet. Companies gather a massive amount of data to create rich profiles of their users, trying to understand how they interact with the platform and what are their preferences. However, these profiles do not follow any standard and are usually incomplete in the sense that users provide different subsets of information to distinct platforms. Thus, the quality and quantity of the data vary between applications and tends to inconsistency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…These are referred to as Personal Online Data Stores (pod or pods) and may be offered by public or private parties and differ in their pricing, security features and accessibility [10]. Research has shown that local connected devices, such as smartphones, might also be used as a Solid pod [11]. As the Solid specification prescribes that data should be stored in a standardised and interoperable format (i.e.…”
Section: Solid Architecturementioning
confidence: 99%
“…These are referred to as Personal Online Data Stores (pod or pods) and may be offered by public or private parties and differ in their pricing, security features and accessibility [10]. Research has shown that local connected devices, such as smartphones, might also be used as a Solid pod [11]. As the Solid specification prescribes that data should be stored in a standardised and interoperable format (i.e.…”
Section: Solid Architecturementioning
confidence: 99%